Relationship of biofilm formation and different virulence genes in uropathogenic Escherichia coli isolates from Northwest Iran - Fattahi, Sargol (GMS Hyg Infect Control, 2015)
Background and objectives: The Escherichia coli (E. coli) bacterium is one of the main causative agents of urinary tract infections (UTI) worldwide. The ability of this bacterium to form biofilms on medical devices such as catheters plays an important role in the development of UTI. The aim of the present study was to investigate the possible relationship between virulence factors and biofilm formation of E. coli isolates responsible for urinary tract infection. Materials and methods: A total of 100 E. coli isolates isolated from patients with UTI were collected and characterized by routine bacteriological methods. In vitro biofilm formation by these isolates was determined using the 96-well microtiter-plate test, and the presence of fimA, papC, and hly virulence genes was examined by PCR assay. Data analysis was performed using SPSS 16.0 software. Results: From 100 E. coli isolates isolated from UTIs, 92% were shown to be biofilm positive. The genes papC, fimA, and hly were detected in 43%, 94% and 26% of isolates, respectively. Biofilm formation in isolates that expressed papC, fimA, and hly genes was 100%, 93%, and 100%, respectively. A significant relationship was found between presence of the papC gene and biofilm formation in E. coli isolates isolated from UTI (P<0.01), but there was no statistically significant correlation between presence of fimA and hly genes with biofilm formation (P<0.072, P<0.104). Conclusion: Results showed that fimA and hly genes do not seem to be necessary or sufficient for the production of biofilm in E. coli, but the presence of papC correlates with increased biofilm formation of urinary tract isolates. Overall, the presence of fimA, papC, and hly virulence genes coincides with in vitro biofilm formation in uropathogenic E. coli isolates.